NILAI TAMBAH PENGOLAHAN BUAH STROBERI MENJADI JUICE DOUBLE BERRY (STUDI KASUS COFFE D’MOOAT DI DESA MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR) - Sombuk, Dormina Mike; Loho, Agnes Estephina; Kaunang, Rine . (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze the added value of strawberry processing into double berry juice atÂ Caffe Dâ€™Mooat in Mooat Village, East Bolaang Mongondow Regency. The research location wasÂ chosen deliberately, namely the area that cultivated strawberries in Bolaang Mongondow TimurÂ District, Mooat Village. This research was conducted from August to October 2018. The CaffeÂ Dâ€™Mooat research site was in Mooat Village, Bolaang Mongondow Timur Regency. The data usedÂ are primary data and secondary data. Primary data is data obtained from observations and directÂ interviews with the owner of Caffe Dâ€™Mooat (one respondent) based on the questionnaireÂ (questionnaire) that had been prepared previously. Secondary data was obtained from CaffeÂ Dâ€™Mooat’s profile, local bookstore, internet through google scholar to get electronic books, journalÂ articles and thesis related to the topic of research on the added value of strawberry fruit. The methodÂ used in this study is a case study method. Data obtained were analyzed using value added accordingÂ to the method of Hayami et al. (1987). The results of this study indicate that in one process theÂ production of double berry juice provides added value of Rp. 68.54/gram.*eprm